NEPAL’S REAL ESTATE LANDSCAPE: UNVEILING BEHAVIORAL DYNAMICS FOR STRATEGIC INVESTMENTS - Paudel, Ram; Yedgarian, Ph.D., Vahick A. (UTSAHA: Journal of Entrepreneurship, 2024)
This study delves into the intricate dynamics of behavioral biases and their consequential effects on individual investment decisions within the real estate sector in Nepal. Through a comprehensive examination of existing literature, this research identifies prevalent behavioral biases among investors, including the illusion of control, cognitive dissonance, herd instinct, hindsight, and representativeness biases. Employing a descriptive research design, content analysis of scholarly articles elucidates the significant influence of these biases on investment decisions. The findings underscore a strong correlation between behavioral biases and investment choices, with notable biases such as loss aversion, self-attribution, regret aversion, and over-optimism prominently shaping investors’ attitudes towards real estate investments. Moreover, the study highlights the pervasive impact of optimistic outlooks on future returns and the herd mentality, wherein investors are driven by peer actions, contributing to the burgeoning real estate market in Nepal. This research provides valuable insights into the underlying behavioral mechanisms driving investment decisions, offering implications for investors, policymakers, and practitioners in mitigating biases and fostering informed decision-making in the real estate domain.